"A slow-motion world" as a manifestation of Alice in Wonderland syndrome: a case report - Almeida, Laryssa Crystinne Azevedo; Valença, Marcelo Moraes (Headache Medicine, 2017)
This article aims to report the case of a female patient suffering from migraine who presented two episodes of distortions in the perception of time concomitantly with the migraine episodes. The sensations experienced by the patient fall within the symptoms described in Alice in Wonderland Syndrome. The feeling that the "world is in slow motion" is a rare form of presentation of Alice´s Wonderland Syndrome.